(untitled) (Bioscience Journal, 2026)
Harvest timing affects both physical and physiological characteristics of cowpea (Vigna unguiculata) seeds. This study aimed to evaluate the influence of harvest periods on the physical and physiological quality of seeds. It also assessed the initial development of Vigna unguiculata cv. Corujinha seedlings. Experiment I took place in the field, using a randomized block design during twelve harvest periods (57, 65, 71, 78, 85, 92, 99, 106, 113, 120, 127 DAS, and a single harvest) with four replications. Experiment II was carried out in the laboratory using a completely randomized design. It analyzed germination (%) and the germination speed index (GSI). After each harvest, evaluations included the number of seeds per pod, pod and seed biometry and moisture content, germination percentage, GSI, seedling length and dry mass, and fungal incidence in seeds. Biometric analysis revealed significant differences. The best pod length was at 120 DAS and 127 DAS, width at 57 DAS and between 85 and 113 DAS, and thickness at 92 DAS. The longest seed length was observed between 92 and 120 DAS, the width between 85 and 113 DAS, and the maximum thickness between 85 and 99 DAS. Single-harvest samples showed higher fungal incidence. They also recorded lower germination and seedling growth values. The maximum dry mass for pods and seeds occurred between 71 and 99 DAS, and in the single harvest. Staggered harvesting reduces seed exposure to field conditions. This enhances seed quality and initial seedling development.